The Effect Of Giving Lemon Aromatherapy To Reduce Menstrual Pain (Dysmenorrhea) In Class X Female Students (Montong District, Tuban Regency) - Kumarijati, Endah Nurul; Istiqomah (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Background: Dysmenorrhea has a high impact on women's lives, resulting in restrictions on daily activities, lower academic achievement in adolescents, and poor sleep quality, as well as causing anxiety and depression . .Objective : This study aims to determine the effect of lemon aromatherapy on female students who experience dysmenorrhea. .Method: This study uses the Pre Experiment method. One Group Pretest – Posttest. Sampling using Accidental sampling technique with a sample of some female students of class X SMAN 1 Montong who experienced dysmenorrhea as many as 16 students a. The independent variable is lemon aromatherapy, the dependent variable is menstrual pain ( dysmenorrhea ). The instrument used was a questionnaire. Data analysis used the Wilcoxon Test statistical test. .Result: Result study Respondent Which experiencing dysmenorrhea, before being given lemon aromatherapy, some big 10 (62.4%) face Moderate dysmenorrhea and after given aromatherapy, part big 13 (81.3%) face dysmenorrhea light. Results test Wilcoxon with significance level α=<0.05 is proven to reduce dysmenorrhea with a value of ???? = 0.000<0.05 which means H 1 accepted so that there is an effect of giving lemon aromatherapy to overcome menstrual pain (dysmenorrhea) in female students of class X SMAN 1 Montong (Montong District, Tuban Regency). ,Conclusion: The conclusion of this study it can be seen that there is the effect of lemon aromatherapy on reducing dysmenorrhea. One alternative way what students who experience dysmenorrhea can do is using aromatherapy which is practical to use, relatively inexpensive, and makes other people feel happy